The effectiveness of gamification using Wordwall on reading skills among kindergarten students (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to explore the effectiveness of employing gamification through the Wordwall platform in enhancing reading skills among kindergarten children. A randomly selected sample of 18 children from Al-Misk Kindergarten in Makkah was divided equally into two groups: an experimental group and a control group, with 9 children in each. The research adopted a quasi-experimental design, and the measurement tool consisted of an achievement test designed to assess three core reading skills: letter position recognition, word formation, and word analysis.The results revealed statistically significant differences in the post-test outcomes in favor of the experimental group that received instruction via gamification using Wordwall, indicating the platform’s positive impact on improving children's reading performance. Furthermore, the experimental group demonstrated notable progress in all targeted skills compared to the control group, emphasizing gamification as an engaging and interactive educational approach that fosters better learning outcomes.The study recommended integrating gamification techniques into early childhood education and developing game-based educational programs to strengthen foundational skills. It also suggested conducting further research to examine the broader impact of gamification across other educational subjects and different academic stages.
Keywords: Gamification; Wordwall Platform; Reading Skills; Kindergarten